The veiled Garvey : the life & times of Amy Jacques Garvey - Taylor, Ula Y. (University of North Carolina Press, 2002)
In this biography, Ula Taylor explores the life and ideas of one of the most important, if largely unsung, Pan-African freedom fighters of the 20th century: Amy Jacques Garvey (1895-1973).
Keywords: Garvey, Amy Jacques.; Garvey, Marcus, -- 1887-1940.; Garvey, Amy Jacques; Garvey, Marcus, -- 1887-1940; Garvey, Amy Jacques -- 1895-1973; African American women political activists -- Biography.; Political activists -- United States -- Biography.; Feminists -- United States -- Biography.; Women intellectuals -- United States -- Biography.; Black nationalism -- United States -- History -- 20th century.; Pan-Africanism -- History -- 20th century.; African American women -- Political activity -- History -- 20th century.; Feminism -- United States -- History -- 20th century.; Femmes activistes noires américaines -- Biographies.; Activistes -- États-Unis -- Biographies.; Féministes -- États-Unis -- Biographies.; Intellectuelles -- États-Unis -- Biographies.; Nationalisme noir -- États-Unis -- Histoire -- 20e siècle.; Panafricanisme -- Histoire -- 20e siècle.; Noires américaines -- Activité politique -- Histoire -- 20e siècle.; Féminisme -- États-Unis -- Histoire -- 20e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; African American women political activists; African American women -- Political activity; Black nationalism; Feminism; Feminists; Pan-Africanism; Political activists; Women intellectuals; United States; African American women political activists -- Biography; Political activists -- United States -- Biography; Feminists -- United States -- Biography; Women intellectuals -- United States -- Biography; Black nationalism -- United States -- History -- 20th century; Pan-Africanism -- History -- 20th century; African American women -- Political activity -- History -- 20th century; Feminism -- United States -- History -- 20th century; 1900-1999; Biography; Biographies; History; Biographies.